Vaccination against SARS-CoV-2 infection among vulnerable and marginalised population groups in Denmark: A nationwide population-based study - Sandra Feodor Nilsson; Thomas Munk Laursen; Merete Osler; Carsten Hjorthøj; Michael E. Benros; Steen Ethelberg; Kåre Mølbak; Merete Nordentoft (Elsevier, 2022)
Summary: Background: Social deprivation, psychiatric and medical disorders have been associated with increased risk of infection and severe COVID-19-related health problems. We aimed to study the rates of SARS-CoV-2 vaccination in these high-risk groups. Methods: Using health, vaccination, and administrative registers, we performed a population-based cohort study including all Danish residents aged at least 15 years, December 27, 2020, to October 15, 2021. Population groups were people experiencing: (1) homelessness, (2) imprisonment, (3) substance abuse, (4) severe mental illness, (5) supported psychiatric housing, (6) psychiatric admission, and (7) chronic medical condition. The outcome was vaccine uptake of two doses against SARS-CoV-2 infection. We calculated cumulative vaccine uptake and adjusted vaccination incidence rate ratios (IRRs) relative to the general population by sex and population group. Findings: The cohort included 4,935,344 individuals, of whom 4,277,380 (86·7%) received two doses of vaccine. Lower cumulative vaccine uptake was found for all socially deprived and psychiatrically vulnerable population groups compared with the general population. Lowest uptake was found for people below 65 years experiencing homelessness (54·6%, 95% confidence interval (CI) 53·4-55·8, p<0·0001). After adjustment for age and calendar time, homelessness was associated with markedly lower rates of vaccine uptake (IRR 0·5, 95% CI 0·5-0·6 in males and 0·4, 0·4-0·5 in females) with similar results for imprisonment. Lower vaccine uptake was also found for most of the psychiatric groups with the lower IRR for substance abuse (IRR 0·7, 0·7-0·7 in males and 0·8, 0·8-0·8 in females). Individuals with new-onset severe mental illness and, especially, those in supported psychiatric housing and with chronic medical conditions had the highest vaccine uptake among the studied population groups. Interpretation: Especially, socially deprived population groups, but also individuals with psychiatric vulnerability need higher priority in the implementation of the vaccination strategy to increase equity in immunization uptake. Funding: Novo Nordisk Foundation.